PENGEMBANGAN MACROMEDIA FLASH 8 PADA TEMA PERTUMBUHAN SI HIJAU UNTUK MENUMBUHKAN BERPIKIR KREATIF SISWA - Dilla Maharani Putri; Lukman Nulhakim; Vica Dian Aprelia Resti (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This study aims to describe the level of validity of Macromedia Flash 8 to foster students' creative thinking. Macromedia flash 8 is to make it easier for students to learn science on the theme of green growth. This research is a type of development research with reference to the opinion of Borg & Gall. The product developed based on the research is macromedia flash 8 for class VII students which contains material about green growth. The research was conducted in a limited way with the subjects for conducting trials in the research being media material experts and science teachers from 2 different schools as practitioners in schools. The data collection technique used was a questionnaire, the questionnaire was used to assess the developed Macromedia Flash 8. The questionnaire contains a number of indicators both in terms of material content and product appearance. The resulting data were analyzed qualitatively and quantitatively. The results of the validity of this study reached 87.50% with very valid criteria.